PENINGKATAN SELF CONFIDENCE DAN HASIL BELAJAR TEMA SELAMATKAN MAKHLUK HIDUP DENGAN TEKNIK CALL ON THE NEXT SPEAKER PADA SISWA KELAS VI MI AL-IMAN TAHUN PELAJARAN 2019/2020 - Lilik Fatkhu Diniyah (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2020)
This research was conducted with the aim to: 1) Describe how to improve self-confidence and learning outcomes of the 6th graders of MI Al-Iman Magelang City with the technique of Call On the Next Speaker. 2) Increase the confidence of the 6th graders of MI Al-Iman students with the Call On The Next Speaker learning technique. 3) Improve the learning outcomes of the theme Save Sentient Beings to the 6th graders of MI Al-Faith with the learning technique of Call On The Next Speaker. This research uses classroom action research (two action research classes). Each cycle is held three times. Each cycle consists of four steps; planning, implementing actions, observing and reflecting. The participants of this study were the 6th graders of MI AL-Iman Magelang academic year 2019/2020. The data obtained consisted of formative test results, observation sheets of teaching and learning activities. From the results of the analysis obtained, the completeness of student learning increased from pre-cycle, cycle I and cycle II, namely pre cycle with an average value of 68 and students who completed 40%, cycle I with an average value of 78 and students who completed by 73%, and cycle II with an average value of 85 and students who completed 100%. While the assessment results obtained student confidence increased from precycle of 20% from 15 students confident when expressing opinions and in the first cycle increased to 60%. then the cycle II increases to 80%. The conclusion of this research is Call Learning Techniques on Speakers Furthermore can improve self-confidence and learning outcomes in the theme of Save Sentient Beings to the 6th graders of MI Al-Iman acadeic year 2019/2020.